Social Network Size and Subjective Well-Being: The Mediating Role of Future Time Perspective Among Community-Dwelling Retirees - Zhang, Zhen; Zhang, Jianxin; Zhao, Na; Yang, Yang (Frontiers in Psychology, 2019)
An accumulating body of literature has confirmed the effect of social networks on the subjective well-being (SWB). However, the relevant mechanism for the relationship between them requires further exploration. This research examined the association between social network size and SWB and the mediating role of future time perspective (FTP) among Chinese retirees. We modeled the relationship between social network size, FTP, and SWB by two sub-studies. SWB was indicated by life satisfaction, positive affect, negative affect, and meaning in life. FTP comprised two dimensions: focusing on opportunity in future and focusing on limitation of time. Study 1 used the number of Spring Festival greeters, and Study 2 used the size of networks based on common actions (discussion, mutual helping, and social participation) as indicators of network size to examine the association and mediating effect among 1097 and 335 community-dwelling retirees, respectively. Both studies revealed that social network size was positively associated with SWB; FTP-opportunity but not FTP-limitation mediated above associations, when possible confounding variables were controlled for. Findings confirm relevance of social networks in the SWB of retirees, and provide a new insight into the role of FTP as an explanatory mechanism.